LBO Capital Structure: An Investigation in to European Private Equity Deals between 2004 and 2009 - Gardner, DCD (2010)
This dissertation report provides a recent, up-to-date and extensive investigation and analysis into LBO capital structure. Specifically this study will examine the phenomenon behind the LBO debt complexity by unravelling its composition and understanding through measurement its leverage. A sample of 147 European LBO deals between 2004 and 2009 comprising from within the UK, France and Germany have been taken from the CMBOR. There are three prominent features of this study. Firstly, a detailed collection of capital debt structuring has been broken down. Secondly, a dynamic comparison of leverage ratios over time and country; and lastly, a thorough regression analysis of the factors that may cause significant changes in leverage. Leverage was measured using D/E and D/EV ratios and the latter was found to be more useful in the regression modelling. The laissez faire approach to arranged loan syndications became a result of altered bank’s business models. A market fuelled by dispersed debt risk and consequential lacking transparency spurred them on. However, unknown risk and little trading forced a dry up in the syndicated loan market and a sharp but abrupt fall in the frequency of LBO deals. After all PE is a procyclical industry and the results in this study are consistent with the view that financing availability induces the inherent rise and fall patterns. In line with previous studies, this study has demonstrated that debt market conditions appear to be the main determinants of leverage. Regression results indicated the debt rate, total deal size and year of transaction as significant contributors while little significance was found when other variables were tested.